ANALISIS HARGA POKOK PRODUKSI, NILAI TAMBAH DAN KEUNTUNGAN AGROINDUSTRI KERIPIK TEMPE DI KOTA METRO - Amni Apriyani; Dwi Haryono; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze main production cost, added value, and income of tempe chips agroindustry. This research uses a case study method at three tempe chips agroindustries which are located in Metro City. Therefore, they are chosen purposively by considering the agroindustries are still active to produce.  Respondents of this research are the owners of the tempe chips agroindustries. The field research was conducted in February until March 2019. The data collected in this research are primary and secondary data. Then, data analysis method uses quantitative descriptive analysis. The results showed that main production cost of tempe chips agroindustry is IDR32,874.39 per kilogram. Added values of tempe chips agroindustry show the positive values hence it is feasible to be developed. Tempe chips agroindustries are profitable because of the R/C values of more than 1.Key words: added value, agroindustry, cost, income, tempe chips